THE INFLUENCE OF KNOWLEDGE SHARING, WORK MOTIVATION, AND ORGANIZATIONAL CULTURE ON EMPLOYEE PERFORMANCE AT CV WISATAMA BERAS BASAH LANGKAT - Kasiana Tuti Arli Sihite; Putri Azzahra; Helrick Nyoliman; Indah Ambarita; Harun Lubis; Herlina Novita (ZILLZELL MEDIA PRIMA, 2026)
This study aims to analyze the influence of Knowledge Sharing, Work Motivation, and Organizational Culture on Employee Performance at CV. Wisatama Beras Basah Langkat. The population in this study consists of all employees of the company, with a sample of 85 respondents selected using the saturated sampling technique. Data collection was carried out through the distribution of questionnaires that were tested for validity and reliability. Data analysis was conducted using multiple linear regression with the assistance of SPSS software. The results of partial testing show that Knowledge Sharing (t-value = 12.217; Sig. = 0.000), Work Motivation (t-value = 9.903; Sig. = 0.000), and Organizational Culture (t-value = 8.570; Sig. = 0.000) have a positive and significant effect on Employee Performance. Simultaneously, these three variables have a significant effect, with an F-value of 113.109 and a significance level of 0.000. The coefficient of determination (R Square) value of 0.807 indicates that the independent variables can explain 80.7% of the variance in the dependent variable, while the remaining 19.3% is influenced by other factors outside the scope of this research model.